Micro-encapsulated secretory leukocyte protease Inhibitor decreases cell-mediated immune response in autoimmune orchitis - Guazzone, Vanesa Anabella (2011)
AIMS: We previously reported that recombinant human Secretory Leukocyte Protease Inhibitor (SLPI) inhibits mitogen-induced proliferation of human peripheral blood mononuclear cells. To determine the relevance of this effect in vivo, we investigated the immuno-regulatory role of SLPI in an experimental autoimmune orchitis (EAO) model. MAIN METHODS: In order to increase SLPI half life, poly-ε-caprolactone microspheres containing SLPI were prepared and used for in vitro and in vivo experiments. Multifocal orchitis was induced in Sprague-Dawley adult rats by active immunization with testis homogenate and adjuvants. Microspheres containing SLPI (SLPI group) or vehicle (control group) were administered s.c. to rats during or after the immunization period. KEY FINDINGS: In vitro SLPI-release microspheres inhibited rat lymphocyte proliferation and retained trypsin inhibitory activity. A significant decrease in EAO incidence was observed in the SLPI group (37.5%) versus the control group (93%). Also, SLPI treatment significantly reduced severity of the disease (mean EAO score: control, 6.33±0.81; SLPI, 2.72±1.05). In vivo delayed-type hypersensitivity and ex vivo proliferative response to testicular antigens were reduced by SLPI treatment compared to control group (p=0.05). SIGNIFICANCE: Our results highlight the in vivo immunosuppressive effect of released SLPI from microspheres which suggests its feasible therapeutic use.